Exosomes Derived from miR-146a-5p-Enriched Mesenchymal Stem Cells Protect the Cardiomyocytes and Myocardial Tissues in the Polymicrobial Sepsis through Regulating MYBL1 - Chun Liu; Jianhua Xue; Bo Xu; Aixian Zhang; Lili Qin; Jiajia Liu; Yang Yang (Hindawi Limited, 2021)
Background. At present, the study has confirmed that the mesenchymal stem cell-derived exosomes (MCSs-Exo) possess cardio-protection in sepsis. Nevertheless, the molecular mechanism of the protection of MSCs-Exo in sepsis remains unknown. Therefore, this research is aimed at studying the molecular mechanism. Methods. The effects of MSCs-Exo and miR-146a-5p in LPS-induced cardiomyocytes (H9C2 cells) in vitro were verified by CCK-8, EdU assay, flow cytometry, Western blot assay, and RT-qPCR. The effect of MSCs-Exo in vivo was evaluated by CLP-induced sepsis model. The potential gene in MSCs-Exo was verified by bioinformatics analysis, and the potential target of miR-146a-5p was identified by bioinformatics analysis and luciferase reporter assay. At last, the function of miR-146a-5p and its target genes on LPS-induced cardiomyocytes (H9C2 cells) in vitro was validated by recuse experiment. Results. Our findings revealed that MSCs-Exo could effectively protect cardiomyocytes of inflammation model in vitro and myocardial tissues of sepsis model in vivo. Meanwhile, we found that miR-146a-5p was a potential gene in MSCs-Exo, and MYBL1 was the target gene of miR-146a-5p and negatively regulated by miR-146a-5p. In addition, miR-146a-5p overexpression promoted proliferation and inhibited apoptosis of LPS-induced cardiomyocytes. The rescue experiment demonstrated that miR-146a-5p could effectively repress the inflammatory response of cardiomyocytes via decreasing MYBL1 expression. Conclusion. This study suggests that miR-146a-5p-bearing MSC-derived exosomes may become an effective treatment for sepsis.